PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MELALUI APLIKASI QUIZIZZ PADA PELAJARAN MATEMATIKA DI KELAS X SMA NEGERI 1 KOLANG - Dina Lorenza Situmeang; Nunik Ardiana; Sinar Depi Harahap (JURNAL MathEdu (Mathematic Education Journal), 2022)
Abstract This study aims to develop interactive learning media products through the Quizizz application in mathematics lessons in Class X SMA Negeri 1 Kolang. To see the effectiveness of interactive learning media through the Quizizz application in mathematics lessons in Class X SMA Negeri 1 Kolang. This research was conducted at SMA Negeri 1 Kolang. The research method used is Research and Development (R&D). This study uses the ADDIE development model including Analysis (analysis), Design (design), Development (development), Implementation (implementation), and Evaluation (evaluation). The data collection technique used is observation and lift. The results of this development are in the form of learning media in the form of animated videos. Learning media were validated by validators from 3 expert teams, namely media experts, 91% were obtained in the very good category, material experts were 96% in the very good category. Then the results of student responses or product practicality obtained an average value of 90 with very good achievements. The results of the research conducted showed that the average value of the students' pretest results was 62.06 while the posttest average value was 85.88. then to test the effectiveness of quizizz-based interactive media in learning seen from the acquisition of the N-gain value. the results of the above calculation obtained an N-Gain value of 0.63. Then if you look for the percentage of the N-Gain value obtained by 63%, it can be concluded that the acquisition of the N-Gain value is in the medium classification. Keywords: Development, Media, Learning, Interactive, Quizizz